Security for Microsoft Visual Basic .NET - Robinson, Ed 1967- (Microsoft Press, 2003)
This resource provides best practices, step-by-step code walk-throughs, and concise explanations of key security terms, issues, and jargon to help developers create and run secure code with Visual Basic.
Includes index. - Title from title screen. - Includes link to companion web site. - Title from website (viewed Jan. 19, 2006)
Keywords: Microsoft .NET Framework; Visual Basic; Computer security; Visual Basic (Computer program language); BASIC (Computer program language); Sécurité informatique; Visual Basic (Langage de programmation); BASIC (Langage de programmation); COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Microsoft